Sources of successful participant engagement in a public health research study: A focus on a Latino community - Angel Lomeli; Arleth A. Escoto; Breanna Reyes; Kayleigh Kornher; Keira Beltran-Murillo; Kathia Nuñez; Ariel Cohen; Maria Linda Burola; Isabel Villegas; Scarlet Flores; Ana Perez-Portillo; Norma Porras; et al. (PLoS ONE, 2025)
Background Latino populations remain vastly underrepresented in clinical and translational research. This study aims to characterize the most common sources of successful participant engagement within our sample. Methods Between February 2022 and March 2023, research staff systematically recorded how participants learned about an ongoing study (which we term source of successful participant engagement) designed to co-create and implement a COVID-19 testing program in a U.S./Mexico border community. Demographic characteristics were correlated with each source of participant engagement at the univariate level using a chi-squared test and, if significant, were included in a multinomial logistic regression model to determine the association between participant characteristics and source of participant engagement. Results A total of 2836 individuals responded to questions regarding source of participant engagement; the most common responses were: Word of Mouth (32%), Clinic/Provider referral (32%), and Walk Up to the testing site (21%). Males were 35% less likely than female participants to report having heard of the study through their Clinic/Provider compared to Walk Up (p < .01). Participants <18 years of age were 2.78 times as likely compared to individuals >54 years of age to have learned about the study through Word of Mouth compared to Walk Up (p < .01). Compared to Walk Up, participants who lived outside San Ysidro were 2.36 times more likely to be recruited through their Clinic/Provider (p < .01) and 2.11 times more likely through Word of Mouth (p < .01), compared those in San Ysidro. Education and clinical symptoms were not significantly associated with engagement source. Conclusion Advancing our understanding of sources of successful participant engagement in marginalized communities is necessary to increase equitable participation in clinical and translational research.